Emotion Regulation and Depressive Symptoms Mediate the Association Between Schizotypal Personality Traits and Suicidality in Chinese College Students. Issue 2 (3rd April 2022) - Gong, Jingbo; He, Yuqiong; Wang, Suhong; Liu, Jianbo
Abstract: Objective: The psychological mechanisms underlying the relationship between schizotypal personality traits and suicidality are not understood. This study investigated the association of schizotypal personality traits with suicidality and explored the mediating role of cognitive appraisal and depression in the relationship between those two variables in a sample of Chinese college students. Method: Participants ( N  = 2457) completed the Schizotypal Personality Questionnaire, the Emotional Regulation Questionnaire, the Zung Self-rating Depression Scale, and three questions related to suicidality. Results: The cognitive reappraisal score was lower in the students with suicidality than the students without suicidality, whereas scores for depression and schizotypal personality traits were higher in the students with suicidality than the students without suicidality. Schizotypal personality traits and depression were risk factors for suicidality. Depression mediated the association between schizotypal personality traits and suicidality. Cognitive reappraisal negatively affected symptoms of depression and had a significant mediating effect on the association between schizotypal personality traits and suicidality. Conclusions: Schizotypal personality traits and depression are risk factors for suicidality. Cognitive reappraisal and depression mediate the association between schizotypal personality traits and suicidality.